Praxeologisch-wissenssoziologische Professionsforschung Perspektiven aus Früh- und Schulpädagogik, Fachdidaktik und Sozialer Arbeit - Bohnsack, Ralf; Bonnet, Andreas; Hericks, Uwe (Verlag Julius Klinkhardt, 2022)
This volume brings the fields of school, early childhood education and social work into conversation with each other and, on this basis, asks about general structural conditions and characteristics of professionalized practice. This is achieved on the basis of empirical analyses within the theoretical framework of the sociology of practice and knowledge and on the methodological basis of the documentary method. In this way, commonalities between the fields of action can be empirically reconstructed at a high level of generalization and theoretically discussed.